CALCULATION OF ELECTRONIC PROPERTIES OF LiBX3 (B = Pb AND Sn; X = Br, Cl AND I) CUBIC PHASE BY DENSITY FUNCTIONAL THEORY - Sagala, Junaina Sahputri; Sirait, Ratni; Ong, Russell (Universitas Negeri Medan, 2024)
Perovskite solar cells utilize perovskite as the active material to convert sunlight into electrical energy. Perovskite is a compound with a crystal structure of ABX₃, where A and B are cations, and X is an anion, usually a halide. Research continues to find perovskites with high efficiency. This efficiency is related to the electronic structure, which can be analyzed using Density Functional Theory (DFT). In this study, the electronic structure of cubic phase LiBX₃ perovskites (B = Pb and Sn; X = Br, Cl, and I) is investigated using Quantum ESPRESSO software. Various parameters such as cut-off energy, k-points, and lattice constants were modified to obtain optimal values. From the optimization results, the band gap, DOS, and PDOS values for the six perovskites were obtained. The resulting band gap energy (Eg) are LiPbBr₃ at 1,71 eV, LiPbCl₃ at 1,87 eV, LiPbI₃ at 1,43 eV, LiSnBr₃ at 0,51 eV, LiSnCl₃ at 0,65 eV, and LiSnI₃ at 0,28 eV. These results show that the band gap energy values increase with the change in atomic radius from Sn to Pb and decrease with the change in atomic radius from Cl, Br to I. The electronic structure calculations of LiBX₃ (B = Pb and Sn; X = Br, Cl, and I) show semiconductor properties that have the potential to be used as light-absorbing materials in perovskite solar cells. This study states that LiBX₃ has great potential in solar cell applications and offers a deep understanding of the relationship between crystal structure and its electronic properties.